Improvement of Chemotherapy Solutions Production Procedure in a Hospital Central Chemotherapy Preparation Unit: A Systematic Risk Assessment to Prevent Avoidable Harm in Cancer Patients. - Bourika, Klio; Koutras, Angelos; Kalofonos, Haralambos; Vicha, Anna; Tsiata, Ekaterini; Papadimitriou, Evangelia; Avgoustakis, Konstantinos; Panagi, Zoi (Clinical Medicine Insights: Oncology, 2019)
Objective: This study was designed to reevaluate and improve the quality and safety of the chemotherapy preparation in a Central Chemotherapy Preparation Unit of a Public Hospital. Methods: A failure modes, effects, and criticality analysis (FMECA) was conducted by a multidisciplinary team. All potential failure modes at each stage of the chemotherapy preparation were recorded, and the associated risks were scored for their severity, occurrence, and detectability with a risk priority number (RPN). Corrective actions were suggested, and new RPNs were estimated for the modified process. Results: Failure modes, effects, and criticality analysis and priority matrix construction, revealed that the partial compliance of Unit's premises with international standards (RPNstage: 307), the human errors throughout the compounding (RPNstage: 223)—labeling (RPNstage: 216)—prescribing (RPNstage: 198) steps, and the violation of working protocols by employees (RPNstage: 215), were the most important risks for which either urgent or immediate corrective actions had to be taken. Modifying the procedure through the proposed corrective actions is expected to lead to a significant (71.3%) risk containment, with a total RPNpreparation process reduction from 2102 to 604. Conclusions: Failure modes, effects, and criticality analysis and priority matrix development identified and prioritized effectively the risks associated with chemotherapy preparation allowing for the improvement of health services to cancer patients.